Frequency of Selenomonas noxia in Oral Microbiota of Obese and Normal Weight People in Duhok-Iraq - Qadir, Roshna M.; Abdulrahman, Mahde S. (Science Journal of University of Zakho, 2019)
Obesity represents one of the major problematic health issues worldwide. Recent evidences suggest that obesity is related with the alteration of the oral microbiome. The aim of this study was to measure the salivary bacterial Selenomonas noxia in Duhok population. A total of 155 saliva samples were collected from individuals (aged between 19-35 years) of both genders (86 females and 69 males). The individuals were divided into three groups (obese, overweight, and normal weight) based on their body mass index. Bacterial genomic DNA was extracted from saliva samples. Molecular detections of Selenomonas noxia were performed by the polymerase chain reaction. Among the 155 participants, 34.1% were obese, 26.4% overweight and 39.3% normal weight individuals. The prevalence rate of oral S. noxia among all people was 82.6%. The highest rate of S. noxia was in obese people (86.8%), followed by overweight (85.4%) and normal weight people (77%). The prevalence of S. noxia in overweight people was statistically significant in compare with the normal weight people (p<0.0001). Moreover, the oral carriage of S. noxia was highest among the overweight females (94.5%) followed by obese females (88.9%). However, no significant difference was found compared to males. The result revealed that it is possible to assume that the expansion of S. noxia in saliva is due to obesity. Moreover, the composition of salivary microbiome may lead to the risk that the overweight group is at risk of future obesity. However, further investigations are required with larger sample and participants with different socioeconomic status in order to address the exact link between obesity and oral bacteria. This could lead to a new and promising therapeutic way for improving human's health.